Pengaruh Pola Tanam Padi Itik dalam Menurunkan Populasi Hama dan Gulma pada Tanaman Padi (Oryza Sativa L.) - Amin, Muhammad; Widihastuty, Widihastuty; Batubara, Siti Fatimah (UNIVERSITAS LABUHANBATU, 2024)
Rice (Oryza sativa L.) is one of the main food crops for most Indonesians. Integrated agriculture or mixed agriculture is a concept of agriculture that supports sustainable agriculture by involving crops and animals in the same land to reduce external inputs, due to mutual support between one component and another. This research was conducted with the aim to see the effect of duck rice cropping patterns in reducing pest and weed populations in rice plants (Oryza sativa L.). The research was conducted on farmers' land in Keramat Gajah Village, Galang District, Deli Serdang Regency, North Sumatra Province. An experimental approach was used in the investigation, including treatments both with and without ducks. Ducks were introduced to the paddy field when the plants were 21 days old until the plants were 55 days old. The number of ducks used was 10 ducks per rante (400 m2). The data obtained were tested using paired t-test analysis. The outcomes demonstrated that, whereas the treatment using ducks did not significantly alter the population of gold snails, it did considerably alter the populations of earthworms (10 and 12 WATP) and weeds (8 and 10 WATP). Keywords: ducks, earthworms, gold snails, paddy, weeds